The Central Bank of Iraq in the age of digital currencies (International experiences with hypothetical scenarios) (Entrepreneurship Journal for Finance and Business, 2022)
Central bank digital currencies are the reaction of central banks to illegal digital currencies of all kinds, whether central bank digital currencies are a new tool for monetary policy or just a new factor in global and local markets. It presents banks with unpredictable opportunities and challenges. The research discusses the basic tasks and functions of the central bank in managing the monetary mass. And the global and regional experiences of digital currencies. And dealt with possible scenarios for the issuance of legal digital currencies. The research reached a set of results, the most important of which was that there are three scenarios for the issuance of digital currencies. From the central banks and the wholesale scenario of cross-border payments is the most convincing as it helps to get rid of the inefficiency of payment systems.